(untitled) (Nepal Journal of Environmental Science, 2021)
The contamination of trace elements (TEs) in freshwater sources has become an alarming issue globally. This study evaluates the contamination level of TEs, their spatial distributions, and the health risks in the Ghodaghodi Lake complex, Nepal. Altogether, ten water samples were collected, and As, Ba, Cd, Co, Cr, Cs, Cu, Li, Mn, Ni, Pb, Rb, Sc, Sr, Ti, Tl, V, Y, and Zn were determined by inductively coupled plasma mass spectrometry. The results revealed that Sr, Zn, Cu, As, Sc, and Rb were dominated TEs, contributing to the contamination. The principal component analysis and correlation matrices demonstrated both the geogenic and anthropic origin of the TEs in the lake. The water quality index (WQI=10.08) and hazard indices <1 exhibited that the TEs pose a low risk to human health and, hence the water of the lake was suitable for drinking purposes. However, exposure risk assessment results suggested that children are relatively more vulnerable compared to adults. The outcome of this study will provide new insights to local people and the concerned authorities for the sustainable management of Ramsar listed Ghodaghodi Lake complex.